What Language Should Be Displayed on Product Packaging? How Unconventional Lettering Influences Packaging and Product Evaluation. Issue 1 (1st January 2021) - Wagner, Udo; Charinsarn, Alisara Rungnontarat
Abstract: Practitioners and academics agree that packaging is a communication tool that impacts marketing success. This paper focuses on a specific cue incorporated in product packaging: the use of supplementary unconventional lettering, such as Arabic characters, on a product package with English. Building on the theory of Foreign Language Display, the use of unconventional lettering that is congruent with the product is expected to be favorable if it is interpreted as a quality cue. Additionally, familiarity with the product category moderates this relationship. This paper discusses empirical studies carried out in a developed economy and a developing economy.